STUDY OF THE EFFECT OF USING AUGMENTED REALITY (AR) BASED LEARNING MEDIA IN ISLAMIC SUBJECTS AS AN EFFORT TO IMPROVE STUDENTS' COGNITIVE LEARNING OUTCOMES - Syaqila, Nurul (Proceeding International Seminar of Islamic Studies, 2023)
The process of implementing Islamic education generally uses the method of reading textbooks and practical methods, but this is not optimal. Therefore innovation is needed to develop interesting and interactive learning media. Learning media with Augmented Reality (AR) technology can provide opportunities for students directly to get more detailed information. Augmented Reality (AR) technology is a technology that can be used as a learning medium by combining two or three-dimensional visual objects that can be presented in the real world and displayed in real-time. This technology can be used in practicum-based Islamic education in the subject of knowing hijaiyah letters, performing ablutions, performing prayers, procedures for washing the cadaver, and so on. The use of Augmented Reality (AR) technology as a learning medium can improve student learning outcomes in the cognitive domain which includes students' ability to name, give examples, memorize, understand, distinguish, and determine. This study uses a qualitative approach through the research method of a literature study to support Islamic Education activities with the background of the need for learning innovations following the digital age.